A case report of neglected DDH - Kamisan, Norazian; Zahari, Anis Anwar; Ismail, Imma Isniza; Tengku Ahmad, Tengku Akmal Faris Bin (Borneo Paediatric Lower Limb Symposium 2024, 2024)
Neglected and untreated developmental dysplasia of the hip (DDH) can lead to severe deformities and functional disabilities. It encompasses a spectrum of anatomical abnormalities that affect the development and stability of the hip joint during critical growth periods. These abnormalities range from subtle acetabular dysplasia to more severe cases involving complete subluxation or dislocation of the femoral head.